Experimental and Biological Insights from Proteomic Analyses of Extracellular Vesicle Cargos in Normalcy and Disease. Issue 12 (19th August 2020) - Charest, Al
Abstract: Extracellular vesicles (EVs) offer a vehicle for diagnostic and therapeutic utility. EVs carry bioactive cargo and an accrued interest in their characterization has emerged. Efforts at identifying EV‐enriched protein or RNA led to a surprising realization that EVs are excessively heterogeneous in nature. This diversity is originally attributed to vesicle sizes but it is becoming evident that different classes of EVs vehiculate distinct molecular cargos. Therefore, one of the current challenges in EV research is their selective isolation in quantities sufficient for efficient downstream analyses. Many protocols have been developed; however, reproducibility between research groups can be difficult to reach and inter‐studies analyses of data from different isolation protocols are unmanageable. Therefore, there is an unmet need to optimize and standardize methods and protocols for the isolation and purification of EVs. This review focuses on the diverse techniques and protocols used over the years to isolate and purify EVs with a special emphasis on their adequacy for proteomics applications. By combining recent advances in specific isolation methods that yield superior quality of EV preparations and mass spectrometry techniques, the field is now prepared for transformative advancements in establishing distinct categorization and cargo identification of subpopulations based on EV surface markers. Abstract : Extracellular vesicles (EVs) are a complex and highly heterogeneous population of membranous vesicles that carry a diverse cargo of biologically active molecules. In this review, the most common sources and methods used to isolate EVs and the different technical approaches to analyze the proteomic compositions of EVs are discussed in the context of health and diseases.